Uma abordagem sociocognitiva da construção do conhecimento na aula de alfabetização - Santana, Mônica de Lourdes Neves (2011)
In the reflections developed in this study, we start from the assumption that the construction of knowledge in the literacy classes is socially constructed and historically situated. In this sense, we consider that it is not distributed, but shared by social actors. In our view, the teaching in the literacy classroom should focus on the cognitive and interactive aspects of language. This research has as object of study the socio-cognitive and interactive activities available and operated in the 1st year of primary teaching. The interest of our study focus on the construction of knowledge, showing the work done by children at school. As we assume a sociocognitive posture in the field of construction of knowledge, we recognize that our analysis will have the support of Vygotsky s conceptions ([1934], 1998, 2008), followed by Oliveira (1999), Salomão (1997, 1999), Tomasello (2003), Mondada (1997), among others. This approach gave us the support to analyze the performance of children in the first year in public schools with different socio-economic aspects in socio-cognitive processes. The analysis of class excerpts, together with the diary of notes revealed that prior knowledge and inferences as social practices play an important role in the building of knowledge and how children will realize literacy. The results of this study are derived from a research of qualitative base in which the prior knowledge and inferences function as cognitive tools in understanding the construction of new knowledge.